PENGARUH PEMBIAYAAN MURABAHAH, MUDHARABAH, MUSYARAKAH TERHADAP ROA DI BANK UMUM SYARIAH - Ramadhani, Ivon Novita; Rosyidah, Norma; Hamdan, Ali; Saifuddin, Saifuddin (International Conference on Islamic Studies, 2023)
This research has the objective of discussing to find out the impact of murabahah receivables, mudharabah financing, and musyarakah financing on ROA as an asset in return for Islamic Commercial Banks in 2012-2022. This study used a descriptive method with a quantitative approach using the SPPS 26 tool. The research technique used a purposive side. Data taken annually from the Financial Services Authority (OJK) website. Data analysis used multiple linear regression analysis, t test (partial), and F test (simultaneous). The population of this study is all income and ups and downs of financing in the financial statements of Islamic Commercial Banks. While the sample used is in the form of annual financial reports which contain income from murabahah receivables, Mudharabah financing and musyarakah financing at Islamic Commercial Banks in 2014-2022. The results of the (partial) test are that the three variables murabhah, mudharah, and musyarakah have no effect on the ROA variable. Whereas in the F test (simultaneous) of the three variables murabhah, mudharabah, and musyarakah there is no significant effect on the ROA of Islamic Commercial Banks 2014-2022.